PENGARUH MEDIA PEMBELAJARAN PLAYDOUGH TEIRHADAP PERKEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN DI TK GKPI TARUTUNG KOTA - Harefa, Sefi Putri; Samosir, Rotua; Butar Butar, Mei Lastri E.F. (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2024)
The purpose of this study is to find out how much influence the meidiia playdough teaching  is in the balance of the credibility of children aged 5-6 years of kindergarten GKPI Tarutung Kota.  The data collection tools in this study are observation, interviews, and documentation. The sample in this study is children aged 5-6 years who are divided into two groups, namely group B2 as the experimental group and group B3 as the control group. The hypothesis test in this study is a t-test using the help of the Microsoft Excel  computer program and the SPSS version 21 program. Based on the results of the Posttest test between the experimental group and the control group, there was a significant difference. The results of the experimental group and the control group normality of the sig. (2-tailed) of 0.081 and 0.666 is greater than the significance level of 0.005 and the homogeneity of the Fcal value is 0.050 will be compared with the value of Fcal with the provision of the numerator dk (n1-1; 8-1=7) and the denominator dk (n2-1; 25-24=24) which is 2.42. So it is known that Fcalung < Ftabel (0.050 < 2.42) sig. Based on the results of the t-test, the Equal Varince Assumed value is calculated > ttable (α=0.05; df= 48), namely tcal= 4.736 > ttable = 2.021 or can be seen in the significant value of Equal Varince Ascetic, which is 0.000 < 0.05. It turned out that the ttable > calculation was 4,736 > 2,021, so Ho was rejected and Ha was accepted. This means that the teacher of the playdough is facing the balance of the creativity of children in the age of 5-6 years of GKPIi Tarutung Kota Kindergarten.